Computer-based risk assessment and criminal procedure (Academic Journal of Internal Affairs, 2018)
The authors provide an overview of the computer-based risk assessment tools used in US criminal procedure and prospects for of using such algorithms in the Hungarian criminal justice system.
Keywords: criminal procedure; US; risk assessment